2021
DOI: 10.14202/vetworld.2021.996-1001
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pestivirus in small ruminants in Central Java, Indonesia

Abstract: Background and Aim: Globally, pestiviruses are among the most economically important viral pathogens of livestock. The genus Pestivirus comprises four species, including bovine viral diarrhea virus type 1 and 2 (BVDV-1 and BVDV-2), which infect cattle, border disease virus and classical swine fever virus which infect small ruminants and pigs, respectively. Accumulating evidence suggests that pestiviruses are no longer species-specific, creating new challenges for disease control. In Indonesia, investigations r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(42 reference statements)
1
3
0
Order By: Relevance
“…Analyses of fragments of 5 UTR (275 nt), Npro (504 nt) and NS3 (2049 nt) and NS5B (1038-2157 nt) of BVDV isolates from Banyumas supported the finding that the subgenotype BVDV-1a is circulating in that region, while a recombination of BVDV-1a with BVDV-1c was indicated in an analysis of 1093 nt of the E2 gene [48]. The BVDV-1 genotype was also detectable in the goat population in Central Java in a study on 288 nt of the 5 UTR gene [44].…”
Section: Genetic Diversitysupporting
confidence: 59%
See 3 more Smart Citations
“…Analyses of fragments of 5 UTR (275 nt), Npro (504 nt) and NS3 (2049 nt) and NS5B (1038-2157 nt) of BVDV isolates from Banyumas supported the finding that the subgenotype BVDV-1a is circulating in that region, while a recombination of BVDV-1a with BVDV-1c was indicated in an analysis of 1093 nt of the E2 gene [48]. The BVDV-1 genotype was also detectable in the goat population in Central Java in a study on 288 nt of the 5 UTR gene [44].…”
Section: Genetic Diversitysupporting
confidence: 59%
“…Studies reported ten provinces to be endemic for BVDV in their cattle population and three provinces are suspected to be BVDV endemic. Provinces in Java are endemic areas, as many studies confirmed seroconversion and antigen detection [39][40][41][42][43][44][45][46]. Seroconversion to BVDV was also detected in cattle in Southern Papua, East Nusa Tenggara, West Nusa Tenggara Barat, Bali and Lampung [62,64,65].…”
Section: Prevalencementioning
confidence: 94%
See 2 more Smart Citations